Effect of Using Eye Mask on Sleep Quality in Cardiac Patients: A Randomized Controlled Trial - Babaii; Adib-Hajbaghery; Hajibagheri (Kashan University of Medical Sciences, 2015)
Background Patients in coronary care unit are at risk of sleep deprivation. Sleep deprivation can be associated with increased blood pressure and heart rate, raising the risk of developing cardiovascular problems among patients hospitalized in coronary care unit. Objectives This study was carried out to examine the effect of eye mask on sleep quality in cardiac patients. Patients and Methods In this randomized controlled trial, 60 patients who met the inclusion criteria were selected using a convenient sampling method and randomly allocated into the experimental and control groups. Patients in the control group received routine care. However, in the experimental group, patients received routine care and eye mask for three subsequent nights. In the both groups, the sleep quality was assessed using the Pittsburgh sleep quality index. Data were analyzed by the chi-square test, independent samples t-test, Mann-Whitney U, and Wilcoxon signed-rank tests. Results After the study, the median scores of the subjective sleep quality, the sleep latency, the sleep duration, the habitual sleep efficiency, and the sleep disturbances domains, as well as the median score of overall Pittsburgh sleep quality index in the experimental group were significantly lower than those in the control group (P < 0.05). However, no significant differences were observed between the two groups in terms of the use of sleep medications and the daytime dysfunction domains (P > 0.05). Conclusions Using eye mask can significantly improve the sleep quality in cardiac patients. Therefore, nurses are recommended to use eye mask in combination with current treatments for improving patients' sleep quality.